Invisible neutrino decay at KM3NeT-ORCA - Christoph Andreas Ternes (Zenodo, 2021)
Parallel Flash Talk at the "XIX International Workshop on Neutrino Telescopes" on line - 18-26 February, 2021 Not on behalf of KM3NeT